UMP now known as Universiti Malaysia Pahang Al-Sultan Abdullah - News, Wav (Newswav Sdn. Bhd., 2023)
He said the Yang di-Pertuan Agong Al-Sultan Abdullah Riayatuddin Al-Mustafa Billah Shah had consented to the use of the UMPSA logo and name according to the Federal Government gazette which came into effect on April 14.